PHYSICO CHEMICAL PROPERTIES AND HEAVY METAL CONTENT OF WATER COLLECTED FROM IBRAHIMPATNAM NEARBY VTPS-VIJAYAWADA - G. KRISHNAVENI; T. BHAGYAKUMAR; O. SAILAJA (International Journal of Pharma and Bio Sciences, 2015)
VTPS is one of the major sources for electricity to Andhra Pradesh state. It was located in Kondapalli village in Vijayawada-Hyderabad National Highway. Approximately 13 villages are there around of VTPS. In VTPS electricity is produced by rotating of turbines with steam of Krishna river water. Present paper deals with the impact of pollution on ground water at Ibrahimpatnam nearby VTPS. During investigation ground water is collected from 6 different locations of Ibrahimpatnam to evaluate physicochemical parameters such as pH, Alkalinity, DO, BOD, COD, Chloride, Electrical conductance, Nitrate, Phosphate and heavy metals. The investigation reveals that the six locations have an impact by VTPS effluents on Ground water.